CsSnI3 Solar Cells via an Evaporation‐Assisted Solution Method. Issue 4 (19th February 2018) - Zhu, Pengchen; Chen, Chuanlu; Gu, Shuai; Lin, Renxing; Zhu, Jia
Abstract : The environmental friendly tin‐based perovskite is attracting a lot of attention as a lead‐free alternative in photovoltaic field. However, the uncontrollable quick crystallization of tin‐based perovskite in traditional solution methods makes it challenging to form smooth and pin‐hole free films, resulting in severe surface recombination and current leakage problem. Evaporation method, known as an effective way to produce smooth films with high coverage, has been rarely investigated in tin‐based perovskites. Here, we demonstrate an evaporation‐assisted solution (EAS) method in CsSnI3 system, combining thermal evaporation with solution method, to produce rather uniform, dense and pinhole free CsSnI3 films. Solar cells fabricated by our EAS method show an average power conversion efficiency (PCE) of 1.93% and a best PCE of 2.23%. Abstract : Compared to the traditional one‐step solution method, the evaporation‐assisted solution (EAS) method could fabricate dense and pin‐hole free CsSnI3 film. The elimination of direct contact of hole and electron transporting materials can reduce the carrier recombination on the surface. As a result, a CsSnI3 solar cell by EAS method with an efficiency of 2.23% is demonstrated.